KONSEP PENGENALAN SAMPAH PLASTIK KEPADA ANAK USIA DINI DENGAN MEDIA PONSEL DI DAYA TARIK WISATA - I Gusti Ketut, Indra Pranata Darma; Made, Ika Kusuma Dewi (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Tourist attraction as one of the pillars of the rapidly developing tourism industry is an element that plays an important role in people's lives. This tourist attraction has a good role in the economic sector, social to education for the community. The existence of this tourist attraction is inseparable with the generation of plastic waste that is now a part of every community life. The emergence of plastic waste has become a classic problem that must be an important concern for today's society so that it does not become a bad legacy for life in the future. Concern about the generation of plastic waste must start early. Proper education especially in the modern digital era, learning must be packaged in an interesting form. This research is expected to provide a concept form of education for early childhood about plastic waste sorting and can provide awareness in waste management.Â